Case reportThe XmnI polymorphic site 5’ to the gene Gγ in a Brazilian patient with sickle cell anaemia – fetal haemoglobin concentration, haematology and clinical features - Belini Júnior, Édis; D. Cançado, Rodolfo; Domingos, Claudia R.B. (Archives of Medical Science, 2010)
We report a 20-year-old female with sickle cell anaemia and with an HbF concentration of 15.8%. The patient was not using hydroxyurea and was not receiving regular blood transfusions. The patient never had chronic manifestations of sickle cell anaemia, only pain crises of a mild intensity. After laboratory tests, we found that she was homozygous for HbS with the Bantu/atypical haplotype, and was heterozygous for the XmnI site. The influence of the XmnI site on the expression of HbF can explain the amelioration in clinical features in this haplotype association in a case of sickle cell anaemia.